2018
DOI: 10.1007/s13201-018-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and modeling of the groundwater hydrogeochemical quality parameters via geostatistical approaches

Abstract: Geostatistical methods are one of the advanced techniques used for interpolation of groundwater quality data. The results obtained from geostatistics will be useful for decision makers to adopt suitable remedial measures to protect the quality of groundwater sources. Data used in this study were collected from 78 wells in Varamin plain aquifer located in southeast of Tehran, Iran, in 2013. Ordinary kriging method was used in this study to evaluate groundwater quality parameters. According to what has been ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Mg, Cl, P, and NO3 showed strong spatial dependency in both seasons with Cn/C ratio < 25% while SO4, and Fe exhibited moderate dependency between 25% -75% in both seasons as well. In the study conducted by Karami et al, [15] on groundwater modelling, EC and TDS indicated moderate spatial dependence while Cl, Na+, SO42-, Total hardness revealed strong spatial dependency. However, it revealed that groundwater quality are spatially dependent.…”
Section: Spatial Dependency Resultsmentioning
confidence: 90%
“…Mg, Cl, P, and NO3 showed strong spatial dependency in both seasons with Cn/C ratio < 25% while SO4, and Fe exhibited moderate dependency between 25% -75% in both seasons as well. In the study conducted by Karami et al, [15] on groundwater modelling, EC and TDS indicated moderate spatial dependence while Cl, Na+, SO42-, Total hardness revealed strong spatial dependency. However, it revealed that groundwater quality are spatially dependent.…”
Section: Spatial Dependency Resultsmentioning
confidence: 90%
“…Because it requires the fewest assumptions and the least knowledge, it was deemed as the "work horse" of practical geostatistics and will serve in some 90% of cases [60]. Research has shown that kriging would in general be more effective than other methods of interpolation if there is spatial autocorrelation among the sampled data points [61][62][63]. In order to minimize the bias, each of the sampling approaches was performed 100 times.…”
Section: Comparing the Correlation And Rmse Between The Predicted Surface Based On Sample And Ndvi Imagementioning
confidence: 99%
“…Eighteen (18) water samples were collected from boreholes in Rumuola community for this study. The sampling points were distributed around the community with the aid of the GIS software.…”
Section: Sampling Techniquementioning
confidence: 99%
“…Kriging which is linear interpolation method, presupposes a statistical model and has standard errors that measure the level of uncertainty of the values that have been forecasted [16,17,18]. Classical kriging assumes that the variogram estimated initially is the correct variogram of the studied data but, this assumption is not always true in practice and this is why EBK was introduced [16].…”
Section: Introductionmentioning
confidence: 99%